2016
DOI: 10.3389/fimmu.2016.00627
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in the Hygiene Hypothesis: The Interplay between Vitamin D, Vitamin D Receptors, Gut Microbiota, and Immune Response

Abstract: The hygiene hypothesis postulates that higher levels of cleanliness and improper exposure to microorganisms early in childhood could disturb the intestinal microbiome resulting in abnormal immune responses. Recently, more attention has been put on how a lack of sun exposure and consequently vitamin D deficiency could lead to less immune tolerance and aberrant immune responses. Moreover, vitamin D receptor (VDR) function has been positioned to be a critical aspect of immune response and gut homeostasis. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 113 publications
0
113
0
7
Order By: Relevance
“…18,56 A consensus in considering vitamin D an anti-inflammatory molecule should raise the question of how and when this activity has a basilar role to warrant cell survival. The activity of vitamin D involves the whole brain-gut axis.…”
Section: Role In Innate Immunitymentioning
confidence: 99%
“…18,56 A consensus in considering vitamin D an anti-inflammatory molecule should raise the question of how and when this activity has a basilar role to warrant cell survival. The activity of vitamin D involves the whole brain-gut axis.…”
Section: Role In Innate Immunitymentioning
confidence: 99%
“…1 Epidemiological studies have demonstrated that vitamin D deficiency is associated with various human diseases. 2 Vitamin D absorbed from the diet or produced in the skin after exposure to sunlight is then converted to 25(OH) VD by the liver and to the active vitamin D metabolite 1α,25-dihydroxyvitamin D3 (1,25(OH) 2 D 3 ) by the kidney. 3 The vitamin D receptor (VDR) regulates most of the biological actions of the active vitamin D metabolite, 1α,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Los niveles de la vitamina D son regulados principalmente mediante la exposición a la luz solar (en especial los rayos UVB, en 80 a 90 %) y la ingesta (10 a 20 %), lo que sugiere que ciertas conductas del estilo de vida occidental, como la poca exposición a la luz solar y el bajo consumo de alimentos ricos en vitamina D, predisponen a la deficiencia/insuficiencia en los niveles de esta vitamina y, en consecuencia, a la desaparición de los efectos inmunorreguladores de esta vitamina, incrementando el riesgo de sufrir enfermedades autoinmunes y alergias. 12 En nuestro estudio observamos una relación entre los altos niveles de vitamina D y los de IgE, lo que complementa la asociación no lineal entre las concentraciones de IgE y vitamina D identificada por Hyppönen et al 27 en una cohorte de adultos británicos con polimorfismos en la enzima CYP27B1 (1α hidroxilasa, enzima clave en la conversión de la vitamina D a su forma activa).…”
Section: Discussionunclassified
“…10 Se ha descrito a la vitamina D como una hormona inmunorreguladora cuya influencia sobre las distintas células del sistema inmunológico desempeña un papel importante en la prevalencia y la severidad de las enfermedades alérgicas y algunas otras condiciones inmunológicas como las enfermedades autoinmunes, y que incluso actúa desde antes del nacimiento. 11,12 Los objetivos de este estudio fueron establecer las diferencias entre los ambientes rural y urbano, los patrones dietarios, los niveles de vitamina D y la influencia de estos en el desarrollo de la sensibilización alérgica (atopia) y en los niveles de IgE en niños afrodescendientes colombianos que residen en San Basilio de Palenque y descendientes de palenqueros que viven en Cartagena de Indias.…”
Section: Abreviaturas Y Siglasunclassified
See 1 more Smart Citation